Visual Ostentivity of Cybertext Context: Critical Pragmatic Perspective of Socio-political Hate Speech in Public Spaces - R. Kunjana Rahardi; Winci Firdaus (Balai Bahasa Sulawesi Selatan, 2024)
The purpose of this study is to describe the form and pragmatic meaning of visual ostentivity in the cybertext context of socio-political hate speech in public spaces from a critical pragmatic perspective. This study is a qualitative study. The object of this study is the visual ostentivity of the cybertext context. The research data were excerpts of speech in social media which contain forms and pragmatic meanings of visual ostentivity in the cybertext context. The data source for this study was social media on various platforms found in public spaces, especially virtual public spaces which contain data on visual ostentivity in the cybertext context. Data were collected using the listening method and the listening was carried out using the note-taking technique. Recording was carried out by paying attention to the multimodality-based cybertext context before data classification and typification were carried out. Triangulation was carried out with an investigation model carried out by related experts. Data analysis was carried out by applying distributional methods and equivalent methods, especially extralingual. The distributional analysis method was used to reach the linguistic dimensions of this study. The extralingual equivalent analysis method was used to reach its pragmatic dimensions. The steps of data analysis were identification, classification, interpretation, and ending with the presentation of the analysis results. This study found five forms of visual ostentivity in the cybertext context. The five forms of ostentivity were presented below: (1) Visual Ostentivity in Cybertext Context with Pragmatic Meaning of Insult, (2) Visual Ostentivity in Cybertext Context with Pragmatic Meaning of Blasphemy, (3) Visual Ostentivity in Cybertext Context with Pragmatic Meaning of Mockery, (4) Visual Ostentivity in Cybertext Context with Pragmatic Meaning of Satire, (5) Visual Ostentivity in Cybertext Context with Pragmatic Meaning of Insult.